Implementasi Perlindungan Hukum Terhadap Saksi Pelaku Yang Bekerjasama Dalam Tindak Pidana Korupsi - Muhammad Arif Sulaiman; Tofik Yanuar Chandra; Ramlani Lina Sinaulan (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
The rules and regulations of the law, it doesn't say anything about the criteria for collaborating perpetrator witnesses. In the Circular Letter (SEMA) of the Supreme Court of the Republic of Indonesia, a criterion called the classification of cooperating perpetrator witnesses is given that judges can use to help them decide cases. The method used in this research is normative legal research, which is done to get the information we need to solve the problem. The results of the study said that witnesses who helped were automatically protected by the law. This is the power of the LPSK. It's very important for different institutions to work together to find witnesses who will help until the perpetrators get a light sentence and get remission and other rights when they do.